The dynamic interactions between cellular-molecular physiology and the environment - The unicellular state as the level of selection - epigenetics - Torday, John S. (Henry Stewart Talks, 2016)
Select epigenetic ‘marks’ are retained from generation to generation, Inter- and transgenerational transmission of epigenetic marks is via germline cells, ~97% of human genetic diseases are likely caused by epigenetic inheritance, Epigenetics allows for redefinition of terms in descriptive biology, Epigenetic inheritance leads to the zygote as the primary level of selection, The cellular-molecular approach to biology is predictive